Designing LED lights for a robot to communicate gaze. (18th April 2019) - Song, Sichao; Yamada, Seiji
ABSTRACT: Eye gaze is considered to be a particularly important non-verbal communication cue. Gaze research is also becoming a hot topic in human–robot interaction (HRI). However, research on social eye gaze for HRI focuses mainly on human-like robots. There remains a lack of methods for functional robots, which are constrained in appearance, to show gaze-like behavior. In this work, we investigate how we can implement gaze behavior in functional robots to assist humans in reading their intent. We explore design implications based on LED lights as we consider LEDs to be easily installed in most robots while not introducing features that are too human-like (to prevent users from having high expectations towards the robots). In this paper, we first developed a design interface that allows designers to freely test different parameter settings for an LED-based gaze display for a Roomba robot. We summarized design principles for well simulating LED-based gazes. Our suggested design is further evaluated by a large group of participants with regard to their perception and interpretation of the robot's behaviors. On the basis of the findings, we finally offer a set of design implications that can be beneficial to HRI and HCI researchers. GRAPHICAL ABSTRACT: